Study of the Biology of Growth and Reproduction of Sphyraena sphyraena in the Syrian Marine Waters(Tartu’s) - غنوم جلال; زهير المجيد; محمد حسن (Latakia University Journal -Biological Sciences Series, 2024)
The growth and reproduction of Sphyraena sphyraena were studied in the Syrian Marine Waters (Tartu’s)during the period from August 2012 to May 2014. Bimonthly samples were collected, a total of 329 fish using of gill nets and longlines were taken for study. Sex ratio (males: females) was (0.83: 1.00). Size at first sexual maturity for males and females was 26.7-27.6 cm. TL 66.8 and SL 58.2. The maximum age 14 year. Spawning season extended from April to Joly. The average fecundity estimates range from (46552- 104216) eggs. The minimum size of ripe ova was 0.97mm.